Optical properties of a retroreflecting sheet. - O'Brien, D; Faulkner, G; Edwards, D (Optical Society of America Inc., 1999)
The power reflection and polarization properties of a close-packed array of retroreflectors are modeled, and a commercially available sheet is measured to verify the predictions. The modeling technique is conceptually simple and applicable to a wide range of structures of this type. The close-packed sheet retroreflects over a range of angles of incidence of approximately -40 to 40 deg in both directions and returns the polarization that illuminates it largely unchanged. Predictions of returned power are within 10% for light incident within 15 deg of normal and within 20% for angles less than 20 deg. Angles of polarization rotation are predicted to within 10 deg over a similar range of input angles. The model predicts the angular aperture of the sheet and the major features of the angular response. Future research will focus on design of structures with wider angles of acceptance and responses optimized for specific applications.